Correlation between nutritional status, leukocyte levels, and neutrophil-lymphocyte ratio to the incidence of respiratory failure in children under five years of age with pneumonia at Abdoel Wahab Sjahranie Hospital, Samarinda - Ainurfaiz Fiqridiyanto; Rachmi, Eva; Muhyi, Annisa (Medical Faculty of Brawijaya University, Indonesia, 2024)
Background: The most common infectious infection-related fatality in children under five worldwide is pneumonia, an acute infection of the lung parenchyma. Hypoxemia can induce respiratory failure and pneumonia-related deaths. For children with pneumonia under five years old, several possible predictors, including nutritional status, leukocyte counts, and the neutrophil-lymphocyte ratio (RNL), can be used to forecast respiratory failure. Because these three criteria are common tests that can be employed in basic healthcare institutions, they are promising predictors. This study aims to determine the relationship between nutritional status, leukocyte levels, and RNL on the incidence of respiratory failure in children under five years of age with pneumonia at Abdul Wahab Sjahranie Hospital, Samarinda. Methods: The research design is case-control. All children with pneumonia under five years old receiving treatment at Abdul Wahab Sjahranie Hospital Samarinda from January to December 2022 made up the study population. Purposive sampling was used to carry out the sampling. The patient's medical record provides the information. Independent T-test and Chi-square test were used to assess the data. Forty patients in all; 20 were case samples, and 20 were control samples. Results: The results showed that the incidence of respiratory failure was related to nutritional status (OR=0.07; p=0.000; 95% CI 0.01 – 0.35), leukocyte levels (OR=35.28; p=0.000; 95% CI 3.86 – 321.98), and neutrophil-lymphocyte ratio (p=0.036). Conclusion: Malnutrition and poor nutritional status, high leukocyte levels, and high RNL have the potential to be predictors of respiratory failure in toddlers with pneumonia.